The ‘Elective Affinity’ of Islamic Populism, Mobilization and Social Media: A Case Study of Indonesian Politic Identity Within the Three Elections - Akmaliah, Wahyudi; Nadzir, Ibnu (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
Scholarly inquiry into Islamic populism in Indonesia has distinctly bifurcated into two primary domains. The first is a comprehensive examination of political issues that explores various perspectives, including political identity, agency, and the influence of political figures. The second domain focuses on the impact of digital platforms, particularly how the proliferation of hoaxes and disinformation plays a critical role in shaping political identities during elections. Unlike previous studies, this article employs Gerbaudo’s concept of elective affinity to elucidate the interconnection between populism in political science and the dynamic realm of social media. These forces generate the political sentiments that shape Islamic populism in Indonesia. Specifically, this article conducts a nuanced analysis, utilizing the presidential elections of 2014 and 2019, as well as the 2017 Jakarta gubernatorial elections, as comprehensive case studies.